Uranium stable isotope fractionation in the Black Sea: Modern calibration of the 238U/235U paleo-redox proxy. (15th April 2017) - Rolison, John M.; Stirling, Claudine H.; Middag, Rob; Rijkenberg, Micha J.A.
Abstract: The isotopic compositions of redox-sensitive metals, including uranium (U), in marine sediments have recently emerged as powerful diagnostic tracers of the redox state of the ancient ocean–atmosphere system. Reliable interpretation of sedimentary isotopic information requires a thorough understanding of the environmental controls on isotopic fractionation in modern anoxic environments before being applied to the paleo-record. In this study, the relationship between ocean anoxia and the isotopic fractionation of U was investigated in the water column and sediments of the Black Sea, the world's largest anoxic basin. Paired measurements of 238 U/ 235 U and U concentration, supported by other redox parameters, were obtained for water column and sediment samples collected during the 2013 GA04N GEOTRACES expedition to the Black Sea. Removal of U from the water column occurs during the redox transition of soluble U(VI) to relatively insoluble U(IV), resulting in up to 43% of U being removed from solution in euxinic bottom waters. Uranium reduction and removal is accompanied by a progressive shift in 238 U/ 235 U towards isotopically light values in the water column as heavier 238 U is preferentially exported to sediments over lighter 235 U. This gives rise to apparent isotope enrichment factors of ε = −0.63 ± 0.09‰ and ε = −0.84 ± 0.11‰ when U removal is modelled by Rayleigh and closed system equilibrium isotope fractionation, respectively. These ε values fall within the range determined for bacterial U reduction experiments, and together with a striking correlation between the distributions of U and H2 S, implicate microbially-mediated U(VI)–U(IV) reduction as the primary mechanism controlling U isotopic shifts in the Black Sea. The 238 U/ 235 U of underlying sediments is related to the the 238 U/ 235 U of Black Sea bottom waters through the isotope enrichment factor of the U reduction reaction but the relationship between sedimentary and water column 238 U/ 235 U is complicated by mass transport processes, and the modelled ε values may underestimate the true isotope enrichment factors. These new results for the Black Sea provide important constraints on the use of 238 U/ 235 U as a proxy of the redox state of ancient oceans.